Effect of a local anesthetic lozenge in relief of symptoms in burning mouth syndrome. (11th January 2016) - Treldal, C; Jacobsen, CB; Mogensen, S; Rasmussen, M; Jacobsen, J; Petersen, J; Lynge Pedersen, AM; Andersen, O
Abstract : Objective: Patients with burning mouth syndrome (BMS) often represent a clinical challenge as available agents for symptomatic treatment are few and often ineffective. The aim was to evaluate the effect of a bupivacaine lozenge on oral mucosal pain, xerostomia, and taste alterations in patients with BMS. Methods: Eighteen patients (4 men and 14 women) aged 39–71 years with BMS were included in this randomized, double‐blinded, placebo‐controlled, crossover trial. Lozenges (containing bupivacaine or placebo) were administrated three times a day for 2 weeks for two separate treatment periods. Assessment of oral mucosal pain, xerostomia, and taste alterations was performed in a patient diary on a visual analog scale (ranging from 0 to 100 mm) before and after the lozenge was dissolved. Results: The bupivacaine lozenge significantly reduced the burning oral pain ( P < 0.001), increased the sense of taste disturbances ( P < 0.001), and had no impact on xerostomia, when adjusted for the treatment period. Conclusions: Our results indicate that the bupivacaine lozenge offers a novel therapeutic modality to patients with BMS, although without alleviating effect on the associated symptoms, taste alterations, and xerostomia.